The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5114/fmpcr.2018.76452
|View full text |Cite
|
Sign up to set email alerts
|

Identification of factors determining anxiety, depression and aggression, with particular emphasis on pain in Polish adolescents and young adults with cystic fibrosis

Abstract: Background. The prolonged survival of patients with cystic fibrosis leads to the search for predictors that determine their physical health and functioning in social and psycho-emotional areas, and allows for better understanding of the mutual interactions. Objectives. The aim of the study was to assess the incidence of pain in patients with CF and clinical determinants of anxiety, depression and aggression. Material and methods. The study covered 95 patients with CF aged 14-25 years. The analysis included: th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In our own research, 60% of respondents stated that immunosuppressive treatment had no effect on their life functions, mentioning at the same time such ailments as mood changes and attention deficit disorders, together with obesity and diabetes, and deterioration of vision, which may be connected with immunosuppressive therapy. In a publication from 2012, more than half of the patients complained about being overweight and hypertension, while claiming earlier that immunosuppressive drugs did not affect their daily functioning [22].…”
Section: Discussionmentioning
confidence: 99%
“…In our own research, 60% of respondents stated that immunosuppressive treatment had no effect on their life functions, mentioning at the same time such ailments as mood changes and attention deficit disorders, together with obesity and diabetes, and deterioration of vision, which may be connected with immunosuppressive therapy. In a publication from 2012, more than half of the patients complained about being overweight and hypertension, while claiming earlier that immunosuppressive drugs did not affect their daily functioning [22].…”
Section: Discussionmentioning
confidence: 99%
“…According to this author, chronic pain is physically and mentally debilitating and as such, it affects the individual's potential for self-care and the performance of daily living activities necessary for personal and economic independence [24]. Cepuch et al identified some factors that determine the emotional disorders (anxiety, depression, or aggression) in patients with cystic fibrosis: pain, female gender, quality of sleep, and body weight [25].…”
Section: Methodsmentioning
confidence: 99%
“…Most reports suggest that the prevalence rates of insomnia are 5% to 15% [2–5] . Insomnia is a chronic problemand has been associated with erectile dysfunction, [6] burning mouth syndrome, [7] depression, [8] anxiety, [9] and functional gastrointestinal disorders [10] . There are many ways to treat or relieve insomnia, including the “guided fantasy” technique, [11] operation of a homeostatic sleep switch, [12] and cognitive behavioral treatments [13] .…”
Section: Introductionmentioning
confidence: 99%